ANALYSIS OF ENVIRONMENTAL KNOWLEDGE RELATIONSHIPS TO THE ATTITUDE OF HOUSEWIVES TO MAINTAIN ENVIRONMENTAL CLEANLINESS - Azizah, Lilik Nur (Transpublika Publisher, 2022)
This research aims to determine the relationship between environmental knowledge and the attitude of housewives in Rusunawa Buring 1, Malang City, toward environmental cleanliness. This research is quantitative research with a survey approach. The population in this study were all housewives in Rusunawa Buring 1 Malang City with a total of 326 people. The sample in this study were 77 housewives obtained through the Slovin formula. Sampling technique using random sampling technique to housewives both working and not working. The data collection technique used a test consisting of 22 questions for the X variable and a questionnaire consisting of 20 questions for the Y variable. The findings reveal that there is a significant influence of the influence of knowledge about the environment on the attitude of housewives in maintaining environmental cleanliness. Keywords: Environmental Knowledge, Housewives Attitude, Environmental Cleanliness,